(untitled) (International Journal of Food and Nutritional Sciences, 2022)
As more and more women are making a shift from corporate workspace to establishing their own businesses, many of them have shown keen interest in promoting sustainable businesses and thereby connecting rural and urban economies as a by-product. This study examines 385 women entrepreneurs based in Delhi NCR exploring their reasons for transition from Corporate to entrepreneurship, the challenges they have faced, and the strategies they are using. Primary data has been collected through survey method on parameters like workplace barriers (glass ceiling), work-life balance, financial independence, and the desire for professional freedom and SPSS has been used as the analytical tool. From the results, it emanates that significant number of women entrepreneurs have ventured into self-owned digital finance enterprises (Green Fintech), and eco-friendly practices. Their businesses help in creating strong value chains between urban markets and rural enterprises. It is encouraging to observe that these women owned sustainable enterprises encourage green investments and use resources efficiently. Going with the entrepreneurial experiences shared by these women, it is clearly evident that more meaningful policies are needed to improve financial access, digital skills, and government support so that sustainable businesses may find their footing in an otherwise volatile market. The findings also indicate that corporate experience and technology-driven rural entrepreneurship can work together not just to promote balanced economic growth but also help in gender equality in India.